2012
DOI: 10.1371/journal.pone.0040489
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scabies Mite Serpins Inhibit the Three Pathways of the Human Complement System

Abstract: Scabies is a parasitic infestation of the skin by the mite Sarcoptes scabiei that causes significant morbidity worldwide, in particular within socially disadvantaged populations. In order to identify mechanisms that enable the scabies mite to evade human immune defenses, we have studied molecules associated with proteolytic systems in the mite, including two novel scabies mite serine protease inhibitors (SMSs) of the serpin superfamily. Immunohistochemical studies revealed that within mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 78 publications
(82 reference statements)
1
62
0
1
Order By: Relevance
“…We previously shown that SMSB4 inhibits the initial and progressing steps of all three complement pathways [25]. In this previous work haemolytic, complement deposition and complement binding assays were employed, where the individual complement pathways were activated by antibody or carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…We previously shown that SMSB4 inhibits the initial and progressing steps of all three complement pathways [25]. In this previous work haemolytic, complement deposition and complement binding assays were employed, where the individual complement pathways were activated by antibody or carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Scabies gut serine protease inhibitors of the serpin superfamily have been found to bind to several plasma proteins in the complement cascades and block the three pathways (classical, alternative and lectin) of the human complement system [19]. Because scabies mites ingest plasma [16], inactivating host complement may protect the mite gut from complement-mediated damage.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the inhibitory mode of action appears to differ between the two SMIPP-Ss future studies evaluating if D1 and I1 act synergistically, perhaps even at lower concentrations, will be of great interest. Previous synergistic studies of scabies mite serpins, that are also anti-complement molecules, did demonstrate synergistic activity [18]. If this is the case with the SMIPP-Ss, a multivalent drug design may need to be considered.…”
Section: Discussionmentioning
confidence: 99%